Preferences and attitudes of the Saudi population toward receiving medical bad news: A primary study from Riyadh city - Mohammed O. Alrukban; Badr O. Albadr; Mohammed Almansour; Waqas Sami; Mussab Alshuil; Abulrahman Aldebaib; Tamim Algannam; Faisal Alhafaf; Abdulaziz Almohanna; Tariq Alfifi; Abdullah Alshehri; Muhannad Alshahrani (Wolters Kluwer Medknow Publications, 2014)
Background: Breaking bad news is one of the most stressful and difficult things a physician has to do. Good communication skills are required in order to ensure that bad news is delivered in a humane but effective way. Objectives: This study was designed to explore the preferences and attitude of the Saudi population toward receiving bad news. Second, it was to identify the associations between preferences, attitudes, and sociodemographic characteristics. Materials and Methods: This was a cross-sectional study conducted during the month of April 2009 in Riyadh. Data were collected from 1013 adult Saudis. Stratified random sampling technique was used through a self-administered questionnaire. Results: In this study, 474 (46.8%) were males and 539 (53.2%) were females. Almost two-third of the participants preferred to be the first to receive the bad news. A majority of the participants 695 (68.6%) preferred to be told the bad news at a private place, whereas, 441 (43.5%) preferred to be told by the head of the medical team. Moreover, almost half of the participants would like the one who breaks the bad news to remain with them to give them some more information about the disease. Significant associations were observed between participants' perception and attitude with age, marital status, gender, and education (P < 0.001), respectively. Conclusion: Factors such as marital status, age, and gender, and education play significant roles in how bad news is received. Understanding what is important in the process of breaking bad news may help in determining how best to perform this challenging task.